2011
DOI: 10.5194/bg-8-2621-2011
|View full text |Cite
|
Sign up to set email alerts
|

Transport and fate of hexachlorocyclohexanes in the oceanic air and surface seawater

Abstract: Abstract. Hexachlorocyclohexanes (HCHs) are ubiquitous organic pollutants derived from pesticide application. They are subject to long-range transport, persistent in the environment, and capable of accumulation in biota. Shipboard measurements of HCH isomers (α-, γ -and β-HCH) in surface seawater and boundary layer atmospheric samples were conducted in the Atlantic and the Southern Ocean in October to December of 2008.HCHs concentrations (the sum of α-, γ -and β-HCH) in the lower atmosphere ranged from 12 to 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 51 publications
(71 reference statements)
2
20
0
Order By: Relevance
“…Xie et al . [] summarized that the air‐water exchange of α‐HCH in the North Atlantic changed from net deposition in 1990 to equilibrium in 1999, and a new equilibrium had established at lower seawater concentrations in 2008. Cai et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al . [] summarized that the air‐water exchange of α‐HCH in the North Atlantic changed from net deposition in 1990 to equilibrium in 1999, and a new equilibrium had established at lower seawater concentrations in 2008. Cai et al .…”
Section: Resultsmentioning
confidence: 99%
“…γ‐HCH was also close to equilibrium in the Bohai Sea, but mainly underwent net deposition in the Yellow Sea as a result of the lower dissolved concentrations. Air‐water exchange direction for γ‐HCH has been dominated by net deposition in most studies [ Xie et al ., ], and this is consistent with the fact that lindane has been globally banned for agricultural use just recently. However, atmospheric concentrations of γ‐HCH might also show greater seasonality and net volatilization could happen in seasons with much lower gaseous concentrations [ Zhong et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…An oceanic air and surface water transfer study of pollutants with hexachlorocyclohexanes Xie et al(2011) already demonstrated the presence of deposition and volatilization processes. Here, we focus on chemical structural changes, depletions and enrichments in the process of primary marine aerosol formation via the bubble bursting process.…”
Section: Resultsmentioning
confidence: 99%
“…Extraction, clean‐up, and analysis of the samples were performed according to the method described elsewhere [ Zhong et al , 2012; Xie et al , 2011]. Briefly, each sample was spiked with the surrogate standard d 6 ‐HCH prior to extraction, then extracted using dichloromethane with MX extractor and purified on a 10% water‐deactivated silica gel column.…”
Section: Experimental Methodsmentioning
confidence: 99%